2013
DOI: 10.1039/c3cs35470a
|View full text |Cite
|
Sign up to set email alerts
|

The development of synthetic antitumour vaccines from mucin glycopeptide antigens

Abstract: Based on important cell-biological and biochemical results concerning the structural difference between membrane glycoproteins of normal epithelial cells and epithelial tumour cells, tumour-associated glycopeptide antigens have been chemically synthesised and structurally confirmed. Glycopeptide structures of the tandem repeat sequence of mucin MUC1 of epithelial tumour cells constitute the most promising tumour-associated antigens. In order to generate a sufficient immunogenicity of these endogenous structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
164
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 73 publications
1
164
0
2
Order By: Relevance
“…In previous work, the synthesis of mucin-type glycopeptides has generally been accomplished by solid-phase peptide synthesis and native chemical or expressed protein ligation methods using glycosylated amino acid building blocks (3). These methods have proved particularly useful for recapitulating mucin structure and function in the context of eliciting an immune response for vaccine development (10). However, the low efficiency and multistep nature of these techniques has restricted peptide size to ca.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, the synthesis of mucin-type glycopeptides has generally been accomplished by solid-phase peptide synthesis and native chemical or expressed protein ligation methods using glycosylated amino acid building blocks (3). These methods have proved particularly useful for recapitulating mucin structure and function in the context of eliciting an immune response for vaccine development (10). However, the low efficiency and multistep nature of these techniques has restricted peptide size to ca.…”
Section: Resultsmentioning
confidence: 99%
“…22 Based on these reports, numerous laboratories have explored innovative approaches to increasing the immunogenicity of MUC1 to develop an immunotherapeutic that could kill cancer cells or even be used in the context of immunoprevention. 2335 Goydos et al demonstrated that a synthetic MUC1-based vaccine could safely be used in humans 36 and a phase I clinical study was reported with a 100 amino acid long MUC1-based vaccine against advanced pancreas and bile duct cancer. 37, 38 In addition, MUC1 peptide pulsed DCs have been used safely as a vaccine in humans with advanced metastatic breast and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The present results may motivate us to challenge the synthesis of various mucin domains towards insights into the significance of the posttranslational glycosylations [10][11][12]39,40 and the discovery of the disease-relevant glycopeptidic epitopes of the antibodies/vaccines against cancers, neurodegenerative diseases, and inflammatory diseases. [41][42][43][44] …”
Section: As Summarized Inmentioning
confidence: 99%